A new species of Taraxacum sect. Arctica (Asteraceae, Crepidinae) from northern Kamchatka, Russia, with a synoptic survey and a nomenclator of the section in Russia - Kirschner, Jan; Štěpánek, Jan; Buryy, Vladimir V.; Chernyagina, Olga A.; Efimov, Petr G. (Phytotaxa, 2022)
Taraxacum sect. Arctica (Asteraceae, Crepidinae) is a circumpolar and alpidic group, relatively satisfactorily explored and studied. It is comprised of more than 55 species, five of them having sexual reproduction (mostly confined to NE Russia and the Aleutians), the majority with agamospermous reproduction. We examined representative material, including types, of almost all taxa formally recognized in the literature, compiled a synoptic survey of T. sect. Arctica in Russia (46 taxa) and a nomenclatural checklist (55 names), and evaluated new collections from Kamchatka. A new species was revealed in the material from northern Kamchatka, distinct in blackish purple to black-violet achenes with sparse and short spinulosity and a very gradual body/cone transition, a short cone, the absence of pollen, and tubular florets. It is newly described as T. atropurpureum.